Application of E-Government in Preventing Illegal Levies in West Java Province - Frans Setia Manonangan Nadeak; Nabila Nabila; Gaston Otto Malindir; Sidrathata Muktar (JURNAL KUASA, 2024)
The importance of implementing E-Government is to create a clean, transparent and accountable government in resolving various problems that occur in society, one of which is illegal levies. The phenomenon of illegal levies is not something new and often occurs in various regions in Indonesia, such as what happened in West Java Province. To resolve the problem of illegal levies, the West Java provincial government is optimizing the implementation of E-government through the Siberli application, which is an online extortion reporting service. This research uses a qualitative research method with a descriptive approach. The choice of this qualitative method was based on the consideration that the application of E-government in eradicating illegal levies in West Java is more appropriately answered with a qualitative descriptive approach. The data collection technique used is through literature study and field study. Meanwhile, the data analysis techniques used include data collection, data processing and drawing conclusions. The results of research in the field show that the implementation of E-government by the government in overcoming the problem of illegal levies in West Java Province is appropriate and relatively effective. This can be seen from data for the last 6 years which shows that the West Java Illegal Levy Saber Task Force has processed at least 60,000 perpetrators of illegal levies. The government's success in overcoming the problem of illegal levies in West Java cannot be separated from the implementation of E-government services, one of which is through the Siberli Application. To provide a deterrent effect to the perpetrators, as many as 42,000 perpetrators were dealt with through direct warnings by the Illegal Levies Saber Task Force, and the remaining 102 other perpetrators were carried out by arrest operations and processed in accordance with applicable legal provisions. Keywords: Electronic Government ∙ Illegal Levies ∙ West Java Province.